Mental imagery and stress: the mediating role of self-efficacy in competitive martial arts athletes - Di Corrado, Donatella; Tortella, Patrizia; Coco, Marinella; Guarnera, Maria; Tusak, Matej; Parisi, Maria Chiara (Frontiers in Psychology, 2025)
IntroductionMartial arts are diverse systems of combat practices, each with its unique techniques, philosophies, and histories. Mental imagery is a multisensory experience that integrates various senses to create vivid mental representations, evoking the physical attributes of people, places, or objects not currently within our perception. In sports contexts, studies have indicated that martial arts often use imagery to enhance performance.MethodsThis study aimed to investigate the mediating role of self-efficacy in the relationship between static (visualizing still scenes or concepts) and dynamic (focusing on motion and action) vividness, controllability (manipulating the imagery experience), and the degree of stress, in a group of 110 martial arts athletes (61 males and 49 females), aged between 21 and 23 years old (M = 22.47, SD = 0.75). Participants were competitive athletes of karate, taekwondo and judo, having a minimum of 13 years of training skill in the sport. They completed the Vividness of Visual Imagery Questionnaire, the Vividness of Movement Imagery Questionnaire-2, the Mental Image Transformation Task, The General Self-Efficacy Scale, and Measuring Psychological Stress Test.ResultsA 2 × 3 (gender × sport type) between groups MANOVA showed significant differences in imagery dimensions by sport type. The results of the mediation analysis showed that self-efficacy plays a mediating role between imagery and stress.DiscussionThe study advanced exploration in the field of mental imagery training, providing additional evidence for its importance in improving performance and managing stress in athletes.